Mycobiome Analysis Reveals High Fungal Richness in Lungs of Acute Respiratory Distress Syndrome after Septic Tank Incident - Verhasselt, Hedda Luise; Kudla, Matthias; Herbstreit, Frank; Weidener, Sophie; Reckinger, Florian; Scholtysik, René; Buer, Jan; Kehrmann, Jan (Archives of Clinical and Medical Case Reports, 2022)
We present a fatal septic tank incident developing acute respiratory distress syndrome and multi-organ dysfunction syndrome. Fungal pathogens complicated the course of disease which were detected by bronchoscopy, microbiologic culture, testing of serum galactomannan and Next-generation sequencing from bronchoalveolar fluid. Mycobiome analysis revealed an unexpected high fungal phylogenetic richness and detected several fungal pathogens reported as causative pathogens for human lung infections that were not detected by traditional microbiological culture. Antifungal microbial therapy should be considered to be included for empiric antimicrobial treatment for septic tank incident patients.